Acute Middle Gastrointestinal Bleeding Risk Associated with NSAIDs, Antithrombotic Drugs, and PPIs: A Multicenter Case-Control Study. - Naoyoshi Nagata; Ryota Niikura; Atsuo Yamada; Toshiyuki Sakurai; Takuro Shimbo; Yuka Kobayashi; Makoto Okamoto; Yuzo Mitsuno; Keiji Ogura; Yoshihiro Hirata; Kazuma Fujimoto; Junichi Akiyama; et al. (PLoS ONE)
Background Middle gastrointestinal bleeding (MGIB) risk has not been fully investigated due to its extremely rare occurrence and the need for multiple endoscopies to exclude upper and lower gastrointestinal bleeding. This study investigated whether MGIB is associated with the use of non-steroidal anti-inflammatory drugs (NSAIDs), low-dose aspirin (LDA), thienopyridines, anticoagulants, and proton-pump inhibitors (PPIs), and whether PPI use affects the interactions between MGIB and antithrombotic drugs. Methods In this multicenter, hospital-based, case-control study, 400 patients underwent upper and lower endoscopy, 80 had acute overt MGIB and 320 had no bleeding and were matched for age and sex as controls (1:4). MGIB was additionally evaluated by capsule and/or double-balloon endoscopy, after excluding upper and lower GI bleeding. Adjusted odds ratios (AOR) for MGIB risk were calculated using conditional logistic regression. To estimate the propensity score, we employed a logistic regression model for PPI use. Results In patients with MGIB, mean hemoglobin level was 9.4 g/dL, and 28 patients (35%) received blood transfusions. Factors significantly associated with MGIB were chronic kidney disease (p<0.001), liver cirrhosis (p = 0.034), NSAIDs (p<0.001), thienopyridines (p<0.001), anticoagulants (p = 0.002), and PPIs (p<0.001). After adjusting for these factors, NSAIDs (AOR, 2.5; p = 0.018), thienopyridines (AOR, 3.2; p = 0.015), anticoagulants (AOR, 4.3; p = 0.028), and PPIs (AOR; 2.0; p = 0.021) were independently associated with MGIB. After adjusting for propensity score, the use of PPIs remained an independent risk factors for MGIB (AOR, 1.94; p = 0.034). No significant interactions were observed between PPIs and NSAIDs (AOR, 0.7; p = 0.637), LDA (AOR, 0.3; p = 0.112), thienopyridine (AOR, 0.7, p = 0.671), or anticoagulants (AOR, 0.5; p = 0.545). Conclusions One-third of patients with acute small intestinal bleeding required blood transfusion. NSAIDs, thienopyridines, anticoagulants, and PPIs increased the risk of acute small intestinal bleeding. However, there were no significant interactions found between antithrombotic drugs and PPI use for bleeding risk.